SERVICE STRATEGY IN INCREASING CUSTOMERS (STUDY: BPRS BAKTIMAKMUR SURABAYA) - Qoriani, Hersa Farida (CV Widina Media Utama, 2022)
Sharia banking is currently viral and its name is soaring, including the Baktimakmur Indah Surabaya Rural Bank (BPRS). There are lots of products in BPRS that are of interest to the people of Surabaya. Therefore, so that customers in BPRS continue to grow and not run to other BPRS, there must be an effective strategy to increase customers. The importance of services at BPRS has an impact on increasing customers. With the strategy especially on service or service makes the customer increase. The purpose of this research is to find out and analyze the right service strategy at BPRS Baktimakmur Indah Surabaya. In this study, the research method used is a qualitative approach with a descriptive research type. Data collection techniques using observation techniques, interviews and documentation. The strategy in providing services must be further improved and provide extra services for customers who have long been members of BPRS Baktimakmur Indah Surabaya. BPRS uses strategies in carrying out services, namely the basic strategy which includes BPRS staff must be able to be friendly and communicative when serving customers, and neat appearance is a form of good service to customers and prospective customers. While the main service strategy includes excellent service, responsiveness, honesty, innovation, and credibility.ABSTRAKPerbankan syariah saat ini memang sedang viral dan namanya sedang melambung tinggi, tak terkecuali Bank Perkreditan Rakyat Syariah (BPRS) Baktimakmur Indah Surabaya. Banyak sekali produk-produk di BPRS yang diminati oleh masyarakat Surabaya. Oleh karena itu, agar nasabah di BPRS terus bertambah dan tidak lari ke BPRS lain, maka harus ada strategi yang efektif untuk meningkatkan nasabah. Pentingnya pelayanan di BPRS berdampak pada peningkatan nasabah. Dengan adanya strategi khususnya pada pelayanan atau service membuat nasabah meningkat. Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis strategi pelayanan yang tepat pada BPRS Baktimakmur Indah Surabaya. Dalam penelitian ini, metode penelitian yang digunakan adalah pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Strategi dalam memberikan pelayanan harus lebih ditingkatkan lagi dan memberikan pelayanan ekstra bagi nasabah yang sudah lama menjadi anggota BPRS Baktimakmur Indah Surabaya. BPRS menggunakan strategi dalam melakukan pelayanan yaitu strategi dasar yang meliputi pegawai BPRS harus mampu bersikap ramah dan komunikatif saat melayani nasabah, dan berpenampilan rapi merupakan bentuk pelayanan yang baik kepada nasabah dan calon nasabah. Sedangkan strategi pelayanan utama meliputi pelayanan prima, daya tanggap, kejujuran, inovasi, dan kredibilitas.